Correlación energética entre la radiación solar global y la velocidad del viento en el caribe colombiano (2021)
Introduction— Nearly 69.18% of Colombian electric matrix (2018) depends on hydraulic resources, which make it vulnerable to rainfall shortage periods, impacting on high energy prices and increasing greenhouse gas emissions due to incorporation of fossil fuel, since these sources contribute with 26.36% to the energy matrix. This led to take actions to expand the participation of Non-Conventional Renewable Energy Sources (NCRES), based on the potential of the different regions where energy sources such as wind, solar and biomass stand out. For large-scale energy production, wind energy and solar energy have great potential in the Caribbean Region; thus, this work intends to assess the wind and solar resources of this region to identify and establish reverse correlation behaviors between them, in order to guarantee that the participation of these energies will maintain the sustainability of the energy matrix by incorporating these energy sources. Objective— Apply a statistical methodology that allow to assess the degree of correlation between the wind and solar resources present in the Caribbean Region, in a time horizon of 5 years (2014-2018). Methodology— Based on data (2014 - 2018) of global solar radiation and wind speed measured on the ground by means of the Automatic Satellite Meteorological Stations (EMAS) from the network of meteorological stations of the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM in spanish), a characterization is carried out through a descriptive analysis in order to obtain a representative value of each variable, the daily and monthly averages of the time series are calculated to evaluate the correlation of each resource separately as joint correlation, using a statistical method based on the calculation of Pearson’s correlation coefficients. Results— The determined time series allow us to understand that the complementarity of the resources separately, such as by combining them, presents a greater number of correlation coefficients close to -1, when the resources are analyzed together, which means that when a resource increases the other is reduced, complementing each other in their behaviors. Conclusions— Both the distance between the measurement points and the temporal resolution modulate the negative correlation presented by the wind and solar resources of the Caribbean Region, consequently continuous availability of resources is obtained by considering a joint utilization